Differential gene expression in Pomacea canaliculata (Mollusca: Gastropoda) under low temperature condition. (31st July 2018) - Liu, Guangfu; Yang, Qianqian; Lin, Huafeng; Yu, Xiaoping
Abstract: Pomacea canaliculata is native to subtropical regions, so its tolerance to low temperatures is a critical factor in limiting its spread into northern areas of China. The snails increase their cold tolerance before winter, but the molecular mechanisms responsible are poorly understood. In this study, we constructed suppression subtractive hybridization (SSH) libraries to identify differentially expressed genes in P. canaliculata exposed to low (0 °C) or normal temperature (25 °C) for 5 days. Both forward and reverse cDNA libraries were constructed. After dot-blot hybridization analysis and sequencing, we obtained 107 and 95 nonredundant differentially expressed sequence tags (ESTs) from the forward and reverse libraries, respectively. Blast2GO analyses indicated that 95 ESTs, 31 from the forward library and 64 from the reverse library, displayed a significant sequence homology to genes with known or putative functions. They were categorized into seven physiological functions including stress resistance, signal transduction, post-translational modification/chaperones, carbohydrate transport and metabolism, energy production and conversion, enzyme regulator activity and translation, and ribosomal structure. To validate the expression profiles from SSH, four differentially expressed genes regulated by low temperature were measured by quantitative real-time PCR. The results showed that expression profiles of the selected ESTs were consistent with the results of differential screening. In addition, time-course expression patterns of the four genes confirmed that the selected genes were differentially expressed in responsive to low temperatures.